Novel pin-jointed connection for cold-formed steel trusses. (January 2016) - Mathieson, Chris; Clifton, G. Charles; Lim, James B.P.
Abstract: Cold-formed steel trusses are a popular form of construction for light-weight buildings, particularly portal frame structures for which spans up to 25 m are increasingly common. A novel pin-jointed truss connector named the Howick Rivet Connector (HRC) has been tested, firstly in a T-joint arrangement, then in a truss assemblage to determine its reliable strength and stiffness. Results show that the HRC performs similarly to a bolted connection in heavy steel in terms of failure modes observed, loads reached and proportionality limit. Finite element models of both T-joints and trusses tested show good agreement with experimental results, particularly in the transition from elastic to inelastic behaviour. Highlights: A series of tests were performed on the novel Howick Rivet Connector. The observed failure modes of the Howick Rivet Connector are ply bearing and shear. The connection strength is comparable to bolted connections of the same diameter. Finite element models showed good agreement with the experimental results.